Political Philosophy : the Narrow Path of Social Progress. - Patton, Anthony C. (Algora Publishing, 2017)
Are there any points where conservatives and liberals can agree? What do we mean by ""social progress"" and how do we know which way to go? How do the values of individual liberty and group loyalty, equal sharing versus reward for achievement, come into play at different stages of civilization's development? The author shows how our shared set of cohesive and consistent values built the successful Western culture we enjoy today, which is what allows us the luxury of helping others to a very great extent. He convincingly argues for the family and private property as key elements in building a s.